A Study of Allelopathy of Some Shade Trees to Coffea arabicaL. Seedlings - Adi Prawoto (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2006)
Because of social economic judgment, many coffee planters nowadays grow Cassia spectabilisand in the certain regions used Cinnamomum burmani, Macadamia integrifolia, Tectona grandisand Cassia siameaas shade trees or intercrops. Before being used in large scale, allelopathy study is appropriate to be done because this effect is much more difficult to be overcome than competiton as growing factor. Research on allelopathy of those species had been conducted in glasshouse of Indonesian Coffee and Cocoa Research Institute using Salisbury & Ross method. Leachate of Cassia spectabilis Cinnamomum burmani, Macadamia integrifolia, Tectona grandisand Cassia siamea, pure media (without plant) and control (well water) were used as treatments. Planting material of Cinnamomum burmani, Macadamia integrifolia, Tectona grandisand Cassia siameawere as seedlings of one year old, whereas C. spectabiliswas 3 months old. Those materials were planted in polybags 20 cm x 30 cm and replicated five times. The media was a mixture of top soil, manure and sand 1 : 1 : 1 (v/v). After those species were maintained for one months and Arabica seedlings for three month old, watering of coffee seedlings then using leachate from shade trees media. Every two days, each seedling was applied with 200 ml. Control was applied with well water. Pure media was used to study the effect of nutrient supply contained in the leachate. The experiment was stopped at seven month old of the coffee seedlings. The result showed that C. spectabilisreleased chemicals which showed allelopathic effect to Arabica coffee, their growth was inhibited 10% to control. The growth decreament from Cassia siameaand D. zibethinustreatment mainly caused by lower mineral content in the leachate and indicated by weak allelopathic. On the other hand M. integrifoliaand C. burmanidid not show allelopathic to Arabica coffee. Thus, based on allelopathy aspect, it can be included that C. spectabilisand C. siamea were not recommended as shade trees or intercrops with Arabica coffee and for D. zibethinusits cropping pattern must be arranged so the mineral competition could be maintained minimum. Key words: Allelopathy, Coffea arabica, Macadamia integrifolia, Cinnamomum burmani, Cassia siamea, Cassia spectabilis, mineral.